Pengaruh Online Customer Review Dan Online Customer Rating Terhadap Keputusan Pembelian Pengguna Marketplace Shopee (Studi Kasus Pada Masyarakat Jakarta Barat) - Dwi Susilowati (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
This study aims to prove and analyze the influence of online customer reviews and online customer ratings on the purchasing decisions of Shopee marketplace users in West Jakarta. This study took statistical quantitative methods and used primary data. The technique used is nonprobability sampling, a type of purposive sampling method by distributing questionnaires online. The research sample amounted to 100 respondents of marketplace users in West Jakarta. This study used the help of IBM SPSS statistical 25 software and used multiple linear regression analysis. This research results in online customer reviews have a partial significant influence on purchasing decisions, online customer ratings have a partial significant influence on purchasing decisions and online customer reviews and online customer ratings have a significant influence simultaneously on purchasing decisions. Then the r2 test shows that as many as 34.1% of online customer reviews and online customer ratings have an influence on purchasing decisions, while as many as 65.9% have the influence of other independent variables.